Comparative Performance between Genetically Improved and Traditional Silver Barb Strain: a Bio-Economic Analysis (Progressive Agriculture, 2013)
Bangladesh Fisheries Research Institute (BFRI) has developed an improved namely, strain silver barb which shows superior performance in terms of growth and production in on-station condition. This paper analyses the comparative performance of improved silver barb strain on an average as well as on an efficient farm. Ordinary least squares regression and tobit models are estimated on an average weight at harvest and the survival rate, respectively to assess the comparative performance of the improved silver barb strain on an average farm. Stochastic frontier functions for weight at harvest are also estimated to assess the comparative performance of the improved strain on an efficient farm. The result shows a superior performance of the genetically improved silver barb strain compared to traditional strain on both average and efficient farms. On an average farm, the improved silver barb strain gives 25% higher body weight at harvest. The breakeven price above variable cost is 4.71% lower for the improved strain. The result shows that the improved silver barb strain has higher potential yield and average yield than the traditional strain.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16577Progress. Agric. 23(1 & 2): 133 142, 2012